Variable speed pump performance characteristics for domestic application - Siti Aisyah, Jilani; Akhtar Razul, Razali (EDP Sciences, 2018)
Generally, water pumps work at a fixed speed. Structural resonance in fixed speed can cause vibration. The reason that most single speed pumps utilize an excessive amount of electricity is that they are overused and oversized. Therefore, this research is embarked to study the characteristic of a pressure-controlled variable speed pump, develop the variable speed pressure controlled pump and analyse the pump performance. A technique is proposed to change the constant speed pump to variable speed pump by adding Variable Frequency Drive (VFD) and microcontroller. A simple test rig is designed and fabricated represented of water distribution for domestic use. The method was then experimentally validated to verify the pump performance and energy used. Data for water flow rate, water pressure, power output and pump speed were analysed. Since the speed can be lowered until 29.27% which according to the water volume demands, therefore the power consumption was found decreased and the lowest power is 0.014 kW. Maximum water discharge capability is 32.38 lpm. It is found that, a variable speed water pump able to save energy up to 97% and led to electricity bill saving and increase the life span of pipes and joints through less hydraulic pressure built-up.